A Retrospective Study on the Effect of STA Anesthesia Technique in the Extraction of Impacted Teeth in Dental Outpatients and Its Impact on Patient Anxiety Levels - Xu J; Su J; Liu G; Ying W; Yuan F (Therapeutics and Clinical Risk Management)
Jie Xu,1,* Junsen Su,1,* Guangfeng Liu,2 Wanggui Ying,3 Fang Yuan4 1Department of Stomatology, High-Tech District, Jinan Stomatological Hospital, Jinan, People’s Republic of China; 2Department of Stomatology, Wendeng Hospital of Traditional Chinese Orthopedics and Traumatology of Shandong Province, Weihai, Shandong, People’s Republic of China; 3Department of Stomatology, Shungeng District, Jinan Stomatological Hospital, Jinan, People’s Republic of China; 4Department of Prosthodontics, Jinan Stomatological Hospital, Jinan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wanggui Ying, Email ywy117@126.com Fang Yuan, Email ynfm053@163.comObjective: To analyze the effect of the Single Tooth Anesthesia (STA) technique in dental outpatient patients undergoing the extraction of impacted teeth and its impact on patient anxiety levels.Methods: This retrospective study included clinical data from 130 patients who underwent the extraction of a single mandibular impacted tooth in our dental outpatient department between April 2022 and June 2024. According to the anesthesia method, patients were divided into two groups: the Traditional Group (n = 65, receiving traditional local injection anesthesia) and the STA Group (n = 65, receiving Single Tooth Anesthesia). Parameters including intraoperative bleeding, duration of anesthesia, extent of anesthetic infiltration, blood pressure [systolic blood pressure (SBP), diastolic blood pressure (DBP)], heart rate (HR), pain [visual analog scale (VAS)], compliance (Frankl treatment compliance scale), tolerance (Houpt behavior scale), and anxiety level [modified dental anxiety scale (MDAS)] were compared between the two groups.Results: There were no significant differences in the amount of bleeding, anesthesia duration, or infiltration range between the two groups (P > 0.05). In the Traditional Group, SBP at 3 minutes after anesthesia and post-extraction was significantly higher than before anesthesia (P < 0.05), whereas DBP and HR showed no significant changes (P > 0.05). In the STA Group, SBP, DBP, and HR remained stable across the three time points (P > 0.05). Compared with the Traditional Group, the STA Group showed significantly lower pain scores, reduced anxiety, and higher rates of treatment compliance and tolerance (P < 0.05).Conclusion: Within the limitations of this retrospective study, the STA anesthesia technique showed advantages over traditional local injection anesthesia in reducing pain and anxiety, while improving compliance and tolerance during impacted tooth extraction in dental outpatients.Keywords: anxiety, impacted tooth extraction, pain, STA anesthesia technique, tolerance